Development and validation of the Chinese version of the self-management support scale for kidney transplant recipients - Keke Lin; Changyun Wei; Jiaqi Li; Xuejie Guo; Fengli Gao; Peiyu Zhao; Hongxia Liu (BMC, 2023)
Abstract Background Providing self-management support to kidney transplant recipients is essential. However, a scale to identify the self-management support they have received is lacking. The purpose of this study is to develop a Self-management Support Scale for Kidney Transplant Recipients (SMSSKTR) and test its psychometric properties. Methods This is an instrument development and validation study, which has a three-stage cross-sectional design. In Stage 1, a preliminary item pool was formed using a literature review, semi-structured interviews, and the Delphi method. In Stage 2, six experts were invited to assess content validity. A convenience sample of 313 participants was used to explore the factor structure by using exploratory factor analysis. The test-retest reliability was assessed using the intra-class correlation coefficient (ICC). In Stage 3, two hundred and sixty-five participants were recruited to validate the factor structure by using confirmatory factor analysis. Convergent validity was examined using Spearman's correlation coefficient. Cronbach's alpha coefficient and corrected item-total correlation coefficient were used to test the reliability of the entire scale and its dimensions. The study was reported according to the STARD and GRRAS checklists. Results An initial 40-item scale was developed in Stage 1. In Stage 2, three factors with 22 items emerged from the exploratory factor analysis: instrumental support, psychosocial support, and relational support. The content validity index of the scale was 0.97. The intra-class correlation coefficient for the entire scale and the subscales were 0.915, 0.771, 0.896, and 0.832, respectively. In Stage 3, the confirmatory factor analysis indicated that the three-factor model had a good fit. The score of the scale was positively associated with that of the Self-Management Scale of Renal Transplant Recipients (r = 0.532). Cronbach's alpha was 0.959 for the entire scale and 0.956-0.958 for the three subscales. The corrected item-total correlation coefficient ranged from 0.62 to 0.82. Conclusion The 22-item SMSSKTR has sufficient psychometric properties to assess the self-management support they have received, which has not been measured before.